Prioritisation and Localisation of Sustainable Development Goals (SDGs): Challenges and Opportunities for Bulawayo - Newman, Peter; Ndlovu, Vinnet; Sidambe, M. (Canadian Center of Science and Education, 2021)
Cities are engines of socio-economic development. This article examines and provides insight into the extent of localisation of the UN’s Sustainable Development Goals (SDGs) using the City of Bulawayo (CoB), in Zimbabwe, as the case study. The key question posited is ‘Does Bulawayo demonstrate potential for sustainable development?’. Bulawayo is a strange case study as in the period of the Millennium Development Goals Zimbabwe had a massive increase in death rates from 2000 to 2010 due to the HIV pandemic, political chaos and economic disintegration of that period. Coming out of that period there was little to help cities like Bulawayo grasp the opportunity for an SDG-based development focus. However, after the paper creates a multi-criteria framework from a Systematic Literature Review on the localisation of the SDG agenda, the application to Bulawayo now generates hope. The city is emerging from the collapse of the city’s public transport and water distribution systems, once the envy of and benchmark for many local authorities in the country, and has detailed SDG plans for the future. Bulawayo now serves as a planning model for localisation of sustainable development goals.